Analysis of Taxation of Property in Bosnia and Herzegovina - Lejla Lazović Pita; Amina Močević (Central European Public Administration Review)
The purpose of this paper is fill in the literature gap and to analyse taxation of property in Bosnia and Herzegovina (BIH). By using IMF and OECD methodology defined under taxes on property, our research tries to compare taxes on property in two BIH entities to the international practice. The results are twofold: firstly, inconsistencies to international classification of taxes on property in BIH are identified and secondly, the taxation of property differs in two BIH entities (RS and FBIH). We find that three different types of property taxes are applied –tax on immovable property in RS and real estate transfer tax and so called tax on property in FBIH. We also find that identified differences have an effect on the size and share of revenues from property taxes in both entities which affect local communities and their revenues. Hence, we focus on property taxes in FBIH since they are under cantonal jurisdiction. The research shows that most revenues from property taxes in FBIH are collected in Sarajevo Canton. In fact, most property tax revenues in Sarajevo Canton come from real estate transfer tax revenues and are collected in four municipalities forming the City of Sarajevo. Bearing in mind lack of reliable long term data in both BIH entities related to taxation of property, we conclude with a few policy recommendations and suggestions for future FBIH property related reforms which should in turn simplify the process of property taxation in FBIH and improve the position of local communities in FBIH.